AGE OF PALAEOZOIC GRANITES AND METAMORPHISM IN THE TUVINO-MONGOLIAN MASSIF OF THE CENTRAL ASIAN MOBILE BELT: LOSS OF A PRECAMBRIAN MICROCONTINENT - Salnikova E.B.; Kozakov I.K.; Kotov A.B.; Kröner A.; Todt W.; Bibikova E.V.; Nutman A.; Yakovleva S.Z.; Kovach V.P. (My University, 2001)
The Tuvino-Mongolian Massif (TMM) was previously interpreted as a Precambrian block within the Central Asian Mobile Belt. According to this idea, it consists of tectonic slices composed of metamorphic rocks of pre-Mesoproterozoic basement that experienced two episodes of regional metamorphism, and Mesoproterozoic ‘cover rocks’ that were reworked together with the basement during high-grade metamorphism. Zircon U–Pb dating of granitoids from all metamorphic complexes demonstrates that the earliest metamorphic event occurred at 536±6 Ma, significantly later than the deposition of the cover rocks. Regional upper amphibolite-facies metamorphism, which affected all metasedimentary units of the TMM, occurred in the short time interval of 497±4 to 489±3 Ma. We propose that there is no simple basement-cover relationship in the Tuvino-Mongolian Massif. Instead, the massif consists of tectonic domains, composed of heterogeneous metasedimentary successions with distinct pre-metamorphic and pre-tectonic histories that were juxtaposed by thrusting prior to 497 Ma and then metamorphosed under upper amphibolite facies conditions. We suggest that this thrusting event was associated with early Palaeozoic collisional processes related to amalgamation of the Central Asian Mobile Belt. Our new model for the evolution of the TMM implies derivation of Neoproterozoic terrigeneous metasediments from ∼800–900 Ma granitoids formed in an Andean-type active continental margin setting.
Keywords: Precambrian; Paleozoic; Tuvino-Mongolian Massif; Палеозой; Paleozoic; Докембрий; Precambrian